The Strengthening of BSTC (Bajulmati Sea Turtle Conservation) in Sea Turtle Monitoring Activities in Gajahrejo Village, Malang Regency. - Setyoningrum, Desy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2024)
Sea Turtles are a type of reptile that predominantly inhabit marine environments, and their populations have experienced a significant decline due to various factors such as natural habitat destruction, marine pollution, predation, and commercial hunting. Conservation efforts are crucial to maintaining the sustainability of turtle populations. The Sea Turtle Conservation Area in Malang Regency, known as Bajulmati Sea Turtle Conservation (BSTC) Malang, has committed to caring for adult turtles, hatching eggs, and nurturing turtle hatchlings. However, these conservation activities have not been fully optimized, particularly in monitoring nesting turtles, rescuing eggs, and addressing turtle diseases. This Community Service Initiative aims to provide knowledge and skills to the conservation area managers related to monitoring, rescuing, and treating turtle diseases. The goal is to enhance the number of saved turtle eggs and improve their survival rate.